Knowledge, productivity, and innovation in Nigeria : creating a new economy - Radwan, Ismail; Pellegrini, Giulia; World Bank. (Washington, DC : World Bank, 2010)
Productivity, and Innovation in Nigeria examines how Nigeria can prepare for this century and where its leaders can focus to achieve their vision, presenting the experiences of other countries from which Nigeria can learn.
Includes bibliographical references (p. 163-166) and index.
rua 07/06/13, ijb, 30/01/2019
Loans
Keywords: Information technology; Human capital; Education; Manpower policy; Nigeria